Analisis Pengaruh Budaya Organisasi dan Lingkungan Kerja Terhadap Kinerja Pegawai dengan Motivasi Kerja Sebagai Variabel Intervening pada Puskesmas Alak Kota Kupang - Efrisca M. Damanik; Stanis Man; Simon Sia Niha; Jou Sewa Adrianus; Anggraeni S. Paridy; David Manafe (JURNAL MANAJEMEN PENDIDIKAN DAN ILMU SOSIAL, 2022)
Abstract: Writing this article intends to find out (1) respondents' perceptions of organizational culture, work environment, work motivation, and employee performance at the Alak Health Center in Kupang City; (2) organizational culture and work environment as long as they influence the work motivation of Alak Health Center employees in Kupang City; (3) organizational culture and work environment influence the performance of employees of the Alak City Health Center in Kupang; (4) work motivation influences the performance of employees of the Alak Health Center in Kupang City; and (5) motivation mediates the influence of organizational culture and work environment on the performance of employees at the Alak Health Center in Kupang City. The sample size in this study, namely 88 informants, used a random sampling technique. The researchers collected data by distributing questionnaires and analyzing using descriptive statistics and inferential statistics (PLS). The results of the descriptive analysis make it clear if the organizational culture, work environment, employee motivation, or employee performance are in a very good category. The results of the inferential analysis clarify the t-test value of organizational culture on work motivation at 0.627, work environment on work motivation at 3.351, organizational culture on employee performance at .296, work environment on employee performance at 2.542, work motivation on employee performance at 3.661, work motivation cannot mediate organizational culture and employee performance of 0.630, work motivation can mediate work environment and employee performance of 2,332. The advice given to the leadership of the Alak Health Center and the Health Office is to continue to disseminate organizational culture, make variations to increase work motivation, and carry out renovations to the Puskesmas to improve service facilities and fulfill all patient needs as well as improve employee performance. Abstrak: Penulisan artikel ini bermaksud guna mencari tahu (1) persepsi responden terhadap budaya organisasi, lingkungan kerja, motivasi kerja maupun kinerja pegawai di Puskesmas Alak Kota Kupang; (2) budaya organisasi dan lingkungan kerja selama memberi pengaruh ke motivasi kerja karyawan Puskesmas Alak Kota Kupang; (3) budaya organisasi dan lingkungan kerja memberi pengaruh ke kinerja karyawan Puskesmas Alak Kota Kupang; (4) motivasi kerja memberi pengaruh ke kinerja karyawan Puskesmas Alak Kota Kupang; dan (5) motivasi memediasi pengaruh budaya organisasi maupun lingkungan kerja pada kinerja karyawan Puskesmas Alak Kota Kupang. Besarnya sampel pada kajian ini, yaitu 88 informan mempergunakan teknik random sampling. Pengumpulan data peneliti lakukan dengan penyebaran kuisioner dan dianalisis mempergunakan statistik deskriptif dan statistik Inferensial (PLS). Hasil analisis deskriptif memperjelas jika budaya organisasi, lingkungan kerja, motivasi pegawai ataupun kinerja karyawan berkategori sangat baik. Hasil analisis inferensial memperjelas nilai uji- t dari budaya organisasi terhadap motivasi kerja sejumlah 0,627, lingkungan kerja terhadap motivasi kerja sejumlah 3,351, budaya organisasi dengan kinerja pegawai sejumlah,296, lingkungan kerja terhadap kinerja karyawan sejumlah 2,542, motivasi kerja terhadap kinerja pegawai sejumlah 3.661, motivasi kerja tidak bisa memediasi budaya organisasi dan kinerja karyawan sejumlah 0,630, motivasi kerja bisa memediasi lingkungan kerja dan kinerja karyawan sejumlah 2.332. Saran yang diberikan untuk Pimpinan Puskesmas Alak dan Dinas Kesehatan untuk terus melakukan sosialisasi Budaya organisasi, melakukan variasi untuk meningkatkan motivasi kerja dan melakukan renovasi Puskesmas untuk perbaikan sarana tempat pelayanan dan melengkapi segala kebutuhan pasien maupun peningkatan kinerja karyawan.